Phased short-interfering RNA siRD29(-) regulates GIBBERELLIN 3-OXIDASE 3 during stolon-to-tuber transitions in potato - Malankar, Nilam; Kondhare, Kirtikumar; Saha, Kishan; Mantri, Mohit; Banerjee, Anjan (Plant Physiology, 2023)
Phased short-interfering RNAs (phasiRNAs) fine tune various stages of growth, development, and stress responses in plants. Potato (Solanum tuberosum) tuberization is a complex process, wherein a belowground modified stem (stolon) passes through developmental stages like swollen stolon and minituber before it matures to a potato. Previously, we identified several phasiRNA-producing loci (PHAS) from stolon-to-tuber transition stages. However, whether phasiRNAs mediate tuber development remains unknown. Here, we show that a gene encoding NB-ARC DOMAIN-CONTAINING DISEASE RESISTANCE PROTEIN (StRGA4; a PHAS locus) is targeted by Stu-microRNA482c to generate phasiRNAs. Interestingly, we observed that one of the phasiRNAs, referred as short-interfering RNA D29(-), i.e. siRD29(-), targets the gibberellin (GA) biosynthesis gene GIBBERELLIN 3-OXIDASE 3 (StGA3ox3). Since regulation of bioactive GA levels in stolons controls tuber development, we hypothesized that a gene regulatory module, Stu-miR482c-StRGA4-siRD29(-)-StGA3ox3, could govern tuber development. Through transient expression assays and small RNA sequencing, generation of siRD29(-) and its phase was confirmed in planta. Notably, the expression of StGA3ox3 was higher in swollen stolon compared to stolon, whereas siRD29(-) showed a negative association with StGA3ox3 expression. Antisense (AS) lines of StGA3ox3 produced more tubers compared to wild type. As expected, StRGA4 overexpression (OE) lines had high levels of siRD29(-) and mimicked the phenotypes of StGA3ox3-AS lines, indicating the functionality of this module in potato. In vitro tuberization assays (with or without a GA inhibitor) using StGA3ox3 antisense lines and overexpression lines of StGA3ox3 or StRGA4 revealed that StGA3ox3 controls the tuber stalk development. Taken together, our findings suggest that a phasiRNA, siRD29(-), mediates the regulation of StGA3ox3 during stolon-to-tuber transitions in potato. A phasiRNA module, Stu-miR482c-StRGA4-siRD29(-), regulates the expression of a gibberellin biosynthesis gene StGA3ox3 during stolon-to-tuber transitions in potato.